RSV PREVENTION IN OLDER ADULTS: A MINI REVIEW OF APPROVED VACCINES - Martyna Sternik; Agnieszka Dobrowolska; Hanna Ćwirko; Zuzanna Drewniak; Marta Rząsa; Karolina Rycman; Adam Skrobarczyk; Kamil Wendrychowicz; Filip Wróbel (International Journal of Innovative Technologies in Social Science, 2025)
Respiratory syncytial virus (RSV) is a major cause of severe respiratory illness, imposing a substantial global health burden on older adults. For decades, the development of a safe and effective vaccine for adults was hindered by challenges, including the experience with an early formalin-inactivated vaccine that caused enhanced disease. A recent advancement in vaccinology, based on structure-guided design of immunogens that stabilize the viral fusion (F) glycoprotein in its prefusion form, has enabled the development and approval of three vaccines for older adults - two protein subunit vaccines: Arexvy, Abrysvo and one mRNA based mRESVIA. This review, based on studies identified through PubMed and Google Scholar using various keywords combinations, introduces the recently approved RSV vaccines, their composition, clinical efficacy, duration of protection, and uptake. Studies have shown that a single dose of these vaccines provides up to 82.6% efficacy against RSV-associated lower respiratory tract disease and 71.7% efficacy against RSV-associated acute respiratory infection within a single RSV season, highlighting their potential to reduce the burden of RSV in this population. As RSV infections continue to pose a significant risk and these vaccines have only been approved within the past two years, it is crucial to raise awareness about preventive measures.